2013
DOI: 10.1038/bmt.2013.79
|View full text |Cite
|
Sign up to set email alerts
|

A novel clofarabine bridge strategy facilitates allogeneic transplantation in patients with relapsed/refractory leukemia and high-risk myelodysplastic syndromes

Abstract: Patients with relapsed/refractory leukemias or advanced myelodysplastic syndrome (MDS) fare poorly following allogeneic hematopoietic cell transplant (HCT). We report prospective phase II study results of 29 patients given clofarabine 30 mg/m2/day i.v. × 5 days followed immediately by HCT conditioning while at the cytopenic nadir. A total of 15/29 patients (52%) were cytoreduced according to pre-defined criteria (cellularity < 20% and blasts < 10%). Marrow cellularity (P < 0.0001) and blast% (P = 0.03) were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…[1][2][3] Previous retrospective and small phase-II studies suggested utility of clofarabine as 'bridge' to transplant in patients with active disease when followed by a reduced intensity conditioning regimen. [4][5][6][7] We sought to confirm these findings by examining survival following a clofarabine bridge to HSCT. Clofarabine is currently approved in the United States for the treatment of acute lymphoblastic leukemia (ALL) in children and has been used off label for the treatment of ALL and AML in adults.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…[1][2][3] Previous retrospective and small phase-II studies suggested utility of clofarabine as 'bridge' to transplant in patients with active disease when followed by a reduced intensity conditioning regimen. [4][5][6][7] We sought to confirm these findings by examining survival following a clofarabine bridge to HSCT. Clofarabine is currently approved in the United States for the treatment of acute lymphoblastic leukemia (ALL) in children and has been used off label for the treatment of ALL and AML in adults.…”
mentioning
confidence: 83%
“…In 2013, Locke et al reported phase II study results in 29 patients with MDS or relapsed/refractory leukemia who received a clofarabine bridge. [5] In this report, 15 of 29 patients (52%) achieved cytoreduction. [5,6] They concluded that disease at the nadir correlated with inferior overall survival and that perhaps successful cytoreduction increased both progression free (330 vs. 171 days) and overall survival (375 vs. 195 days), though neither were statistically significant.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Among the 24 patients evaluable for response, 8 patients (33%) achieved a CR, CRp or marrow CR and 4 (17%) HI, for an ORR of 50%. With a median follow-up of 4.9 months (range 1.9 --16.7 months), the median OS was 4.8 months (range 0.5 --13.5 months) and the 4-week mortality was 12% [41]. Common non-hematologic adverse events were nausea (31%), headache (24%), rash (28%), elevated liver enzymes (41%) and febrile neutropenia (28%).…”
Section: Clofarabine Post-hypomethylating Failuresmentioning
confidence: 96%
“…In addition to providing a valuable treatment option for pediatric patients with ALL, clofarabine alone and in combination with Ara-C also has demonstrated substantial activity against MDS and AML in the older population. Clofarabine can be used as a bridge to transplantation in patients with MDS [41]. The role of clofarabine in MDS will be to improve outcomes by increasing the response rate and decreasing the treatment-related mortality in these patients.…”
Section: Expert Opinionmentioning
confidence: 99%